DISTRIBUSI FUNGSIONAL VERBA PADA KONTEKS PERISTIWA DALAM WACANA NARASI DONGENG BAHASA INDONESIA - Poerwadi, Petrus (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 17 (2010): September 2010, 2010)
Every types of verbs have a specific distribution in the context of event in the written Indonesian tales narrative discourse (WNDBI). That specifics distribution implicate a specific verbs functions and meanings in the context of event in the WNBI. The use of verbs in the context of event in WNDBI are dominated by material-process verbs, relational-process verbs, and mental-process verbs. Types of clauses, internal pattern of clauses embedded by certain types of verbs, and characteristics of participants give effects on the functions and meaning of the clause in WNDBI. The distribution of verbs in WNDBI well dominated by the distribution of verbs in the relational event. The domination of relational event shows that the WNBI gives more explanation of causality and motivation. The domination of relational event also shows that the authors tend not to tell the main stories directly.